2019
DOI: 10.1126/scitranslmed.aat8462
|View full text |Cite
|
Sign up to set email alerts
|

Aβ and tau prion-like activities decline with longevity in the Alzheimer’s disease human brain

Abstract: The hallmarks of Alzheimer’s disease (AD) are the accumulation of Aβ plaques and neurofibrillary tangles composed of hyperphosphorylated tau. We developed sensitive cellular assays using human embryonic kidney–293T cells to quantify intracellular self-propagating conformers of Aβ in brain samples from patients with AD or other neurodegenerative diseases. Postmortem brain tissue from patients with AD had measurable amounts of pathological Aβ conformers. Individuals over 80 years of age had the lowest amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 90 publications
8
95
1
2
Order By: Relevance
“…Currently, cholinesterase inhibitors (AChEIs) and the NMDA receptor antagonist are the only therapies for AD (76). However, these can only relieve symptoms and not delay the progress of AD (77)(78)(79). Moreover, three cholinesterase inhibitors, namely, donepezil, rivastigmine, and galantamine, which are approved by the US Food and Drug Administration, were proven to increase side effects, such as nausea, vomiting, and diarrhea.…”
Section: New Insights Into the Pathogenesis Of Admentioning
confidence: 99%
“…Currently, cholinesterase inhibitors (AChEIs) and the NMDA receptor antagonist are the only therapies for AD (76). However, these can only relieve symptoms and not delay the progress of AD (77)(78)(79). Moreover, three cholinesterase inhibitors, namely, donepezil, rivastigmine, and galantamine, which are approved by the US Food and Drug Administration, were proven to increase side effects, such as nausea, vomiting, and diarrhea.…”
Section: New Insights Into the Pathogenesis Of Admentioning
confidence: 99%
“…37 A self-propagating protein, or prion, should be able to replicate in cell culture and pass from one naïve cell population to another while retaining its pathological characteristics. [63][64][65] However, the potential of ExoY, alone or in conjunction with other T3SS effectors, to generate selfpropagating amyloid cytotoxins has not been determined.…”
Section: Infection-induced Amyloid Cytotoxins Are Self-propagatingmentioning
confidence: 99%
“…Aoyagi et al established a cellular model of tau aggregation by introducing concentrated abnormal tau proteins from AD brains, and reported that insoluble tau from the early stage of AD has a higher seeding activity than that from later stages. 27 Mouse models of tau propagation were developed in 2009 by Clavaguera et al 28 They showed that inoculation of brain homogenates prepared from P301S tau transgenic mice with inclusions into tau mice overexpressing wild-type human tau induced tau pathologies. They also showed that brain homogenates prepared from brains of patients induce tau pathologies in mice similar to those in © 2020 Japanese Society of Neuropathology…”
Section: Propagation Of Tau Proteinsmentioning
confidence: 99%